The Association Between Monocyte Subsets and Cardiometabolic Disorders/Cardiovascular Disease: A Systematic Review and Meta-Analysis - Oh, Ester S.; Na, Muzi; Rogers, Connie J. (Frontiers in Cardiovascular Medicine, 2021)
Background: Monocyte subsets in humans, i.e., classical (CM), intermediate (IM), and non-classical monocytes (NCM), are thought to differentially contribute to the pathogenesis of atherosclerosis, the leading cause of cardiovascular disease (CVD). However, the association between monocyte subsets and cardiometabolic disorders and CVD is not well-understood. Thus, the aim of the current systematic review and meta-analysis was to evaluate recent findings from clinical studies that examined the association between the distribution of monocyte subsets in subjects with cardiometabolic disorders and CVD compared to healthy controls. Methods: Articles were systematically searched in CINAHL, PubMed and Cochrane Library. Articles were independently screened and selected by two reviewers. Studies that reported the percentage of each monocyte subset were included in the systematic review and meta-analysis. For the meta-analysis, a random-effects model was used to generate pooled standardized mean differences (SMD) between subjects with cardiometabolic disorders and healthy controls. Results: A total of 1,693 articles were screened and 27 studies were selected for qualitative analyses. Among them, six studies were included in the meta-analysis. In total, sample size ranged from 22 to 135 and mean or median age from 22 to 70 years old. We found studies that reported higher percentage and number of IM and/or NCM in subjects with cardiometabolic disorders (9 out of 13 studies) and in subjects with CVD (11 out of 15 studies) compared to healthy controls. In the meta-analysis, the percentage of CM was lower [SMD = −1.21; 95% CI (−1.92, −0.50); P = 0.0009; I2 = 91%] and the percentage of IM [SMD = 0.56; 95% CI (0.23, 0.88); P = 0.0008; I2 = 65%] and NCM [SMD = 1.39; 95% CI (0.59, 2.19); P = 0.0007; I2 = 93%] were higher in subjects with cardiometabolic disorders compared to healthy controls. Conclusions: Individuals with cardiometabolic disorders and CVD may have a higher percentage of IM and NCM than healthy controls. Future studies are needed to evaluate the cause and biological significance of this potential altered distribution of monocyte subsets.